Microstructure and mechanical property relationship for different heat treatment and hydrogen level in multi-pass welded P91 steel joint. (August 2017) - Pandey, Chandan; Mahapatra, M.M.; Kumar, Pradeep; Saini, N.; Srivastava, A.
Graphical abstract: Highlights: Effect of diffusible hydrogen level on mechanical properties and Charpy toughness of multi-pass shielded metal arc weld joint of P91 steel plate of 18 mm thickness. Study on effect of post weld heat treatment on microstructure variation, hardness gradient and mechanical properties of P91 steel weldments. Study on effect of normalizing/tempering treatment on microstructure variation, hardness gradient and mechanical properties of P91 steel plate weldments. A comparative study of normalizing & tempering and post weld heat treatment on fracture surface morphology of impact and tensile tested specimen. Effect of diffusible hydrogen level in multi-pass weld and their effect on fractographs of impact and tensile tested specimen. Abstract: The effect of heat treatment condition and diffusible hydrogen level on microstructure and mechanical properties of multi-pass shielded metal arc welded (SMAW) P91 steel butt joints of 18 mm thickness has been studied. Field-emission scanning electron microscope (FESEM), Mercury diffusible hydrogen measurement, Charpy test, room-temperature tensile testing, hardness measurement and energy dispersive X-ray spectroscopy (EDS) were performed to characterize the multi-pass SMAW joints in as-welded, post-weld heat treatment (PWHT) and normalizing/tempering (N&T) state. The P91 steel butt joints with low level of diffusible hydrogen exhibited higher tensile strength and toughness. Both PWHT and N&T treatment provided similar mechanical properties but a significant microstructure variation was noticed for different zones of P91 welds. N&T treatment produced the homogenize microstructure along the P91 weldments both in terms of microstructure and micro-hardness.